Tax Incentive and Taxpayers Awareness Impact on Tax Compliance during COVID-19 Pandemic - Fadilla, Fahri Ahmad; Juhaeni, Heni; Safitri, Mita Alya; Ferthysa, Reginna; Anshori, Reksy Fauzan Putra; Wijaya, Aida (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research aimed to analyze the significance of tax incentive and taxpayers’ awareness impact on tax compliance during COVID-19 in Bandung, Indonesia. The research used primary data and was done by sending questionnaire to subjects of 53 Indonesian who already have tax identification number and have tax obligation. While both tax incentive and taxpayers’ awareness have impact on tax compliance, a regression showed tax incentive has no significant impact, but taxpayers’ awareness significantly impacts tax compliance. This means, it will be more effective for the government to work on taxpayers’ awareness which has significant effect on tax compliance.